Prevalence and Antibiotic Susceptibility Profiling of MDR Pseudomonas aeruginosa from UTI Patients of Southern Punjab, Pakistan - Iqra Arooj; Aysha Asghar; Mehvish Javed; Amina Elahi; Asghar Javaid (RADS Journal of Biological Research & Applied Science, 2022)
Background: Urinary Tract Infections (UTIs) are of major concern in health care settings. An increasing percentage of organisms causing nosocomial infections have now become multidrug resistant. Hence, constant surveillance of etiology and antimicrobial susceptibility of uropathogens including Pseudomonas aeruginosa is compulsory.